The biomecanical analysis of movement`s skills accuracy of smash in badminton of the deaf students - Zola, N.; Rumini, R.; Wahyudi, A. (Journal of Physical Education and Sports, 2021)
The physical condition and movement systems of deaf students are the same as normal students in general. One sport that suits the needs of the deaf to develop their potential is badminton. In badminton, there is a forehand smash, which is an accuracy exercise using the drill method. In addition to the drill method, the biomechanical aspects of the smash motion such as the initial stage, hit and advanced motion determine the accuracy of the smash. The purpose of this study is to analyze the stages of pre-stage, strike and follow-up motion to produce smash accuracy for the deaf students. This type of research is a survey, with a sample of 14 deaf students consisting of 8 male and 6 female aged 16 years and over. Data collection techniques using test methods and recording results. The data analysis uses quantitative descriptive. The result of this research is that the average accuracy of badminton smash hits is in the low category and movement skills are in the adequate category. In the pre-stage of badminton skills, it affects 21% of the accuracy of the smash, the hit stage affects 71% of the accuracy of the smash and the advanced stage of movement affects 50% of the accuracy of the smash. The conclusion from this research is the stage of exposure affects the results of the accuracy of badminton smashes more, so it is necessary to teach more drill exercises and variations of drill smashes to deaf students in order to produce good smash accuracy